A −110 dB THD rail-to-rail class-AB programmable gain amplifier with common-mode-detection-based transconductance linearization scheme. (October 2022) - Tang, Fang; Wu, Nairiga; Yang, Tongbei; Wang, Hao
Abstract: A low total harmonic distortion (THD) programmable gain amplifier (PGA) with dual operational amplifiers (op-amps) for electrocardiogram (ECG) signal acquisition applications is presented. The proposed op-amp comprises the rail-to-rail input stage and class-AB output stage. To solve the transconductance (g m ) variation caused by the supply voltage changes in rail-to-rail amplifiers with the traditional DC level-shifting technique, a common-mode-detection-based transconductance linearization scheme is proposed in this paper, associated with a 7-steps resistor-feedback digital gain control from 1 V/V to 12 V/V, which can realize less than 2.7% transconductance variations. The proposed rail-to-rail class-AB PGA is implemented in 0.18- μ m CMOS technology with 2.7-V ∼ 5-V power supply voltage and 0.07-mm 2 core area. Spice simulation results show that the THD is − 110 dB with an input signal of 5 mV p p and the input-referred noise spectrum density is 0.5 μ V/ H z at a 10-Hz frequency point, after adopting an 8-kHz chopping. The total power consumption including the bias circuit is 81 μ W at 2.7 V.